Influence of the composition on the organization of a layered perovskite-like structure of indates AIILaInO4 - Titov, Yu.A.; Belyavina, N.M.; Slobodyanik, M.S.; Babaryk А.А.; Timoschenko М.V. (Reports of the National Academy of Sciences of Ukraine, 2017)
The phase Sr0.7Ca0.3LaInO4 has been synthesized by heat treatment of co-crystallized nitrates, and its layered perovskite-like structures (LPS) has been determined by X-ray powder diffraction. It is found that Sr0.7Ca0.3LaInO4 is isostructural to SrLaInO4 (sp. gr. Pbca). Influence of the composition on the organization of LPS mono-layered indates AIILnInO4 is established. It has been shown that the substitution of atoms in the A-position by smaller ones in the AIILnInO4 LPS results in an increase of the deformation degree of the (AII, Ln)O9 polyhedra, which destabilizes their LPS.